2020
DOI: 10.1101/2020.02.03.932442
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Consistent Effects of Pesticides on Community Structure and Ecosystem Function in Freshwater Systems

Abstract: 20Predicting ecological effects of contaminants remains challenging because of the sheer number 21 of chemicals and their ambiguous role in biodiversity-ecosystem function relationships. We 22 evaluated responses of pond ecosystems to standardized concentrations of 12 pesticides, nested 23 in four pesticide classes and two pesticide types. We show consistent effects of herbicides and 24 insecticides on ecosystem function, but slightly less consistent effects on community 25 composition. Effects of pesticide… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Few studies have attempted to evaluate how synthetic chemical disturbances in communities are associated with changes in ecosystem functions (Bernhardt et al 2010;Rosi-2014;Rumschlag et al 2020). Our study found that insecticides led to persistent, and non-trivial, increases in ecosystem respiration, while herbicides lead to short-term decreases in ecosystem respiration that varied with pesticide classes.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Few studies have attempted to evaluate how synthetic chemical disturbances in communities are associated with changes in ecosystem functions (Bernhardt et al 2010;Rosi-2014;Rumschlag et al 2020). Our study found that insecticides led to persistent, and non-trivial, increases in ecosystem respiration, while herbicides lead to short-term decreases in ecosystem respiration that varied with pesticide classes.…”
Section: Discussionmentioning
confidence: 79%
“…Further, predicting the effects of pesticides could be simplified if organisms that are taxonomically related or share similar functional roles within an ecosystem have similarities in their responses to pesticides, a trend that has been shown in previous toxicological research (Ippolito et al 2012;Hua & Relyea 2014). For example, our previous research has shown consistency in the effects of pesticides by class and type on parasite transmission, ecosystem functions, and macroinvertebrate and amphibian communities (Rumschlag et al 2019(Rumschlag et al , 2020. In addition, organisms that share functional roles in a community have been shown to respond similarly to types and classes of pesticides (Rumschlag et al 2020).…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations